Land Characteristic and Land Availability for Food Crops to Attain Food Sovereignty in Kabupaten Bandung - Abraham Suriadikusumah (Soilrens, 2018)
Land use change has long been a problem in West Java, especially in Bandung district (Kabupaten Bandung), a hinterland and buffer area for the Bandung Metropolitan and one of the major crop district in West Java province.  Land use conversion caused the decrease of soil productivity and land availability for agricultural activity especially for food crops, the land reduction is unable to compensate the need of food availability.The research in this study has been done by using descriptive and comparative survey method to study land characteristic and status of land availability in Kabupaten Bandung and its contribution food crop development. The results showed that soil fertility status in Bandung district varies from very low to high. Soil pH conditions ranged from acid to neutral. The actual availability of land for food crops currently stands at 52,790 hectares, with paddy fields as current land use. Availability of potential land for food crops are 64,970 hectares with the current type of land use in the form of bushes and plantations.  Keywords: characteristics, availability, land use conversion, land, district Bandung